DİKENLİ TATLISU YILAN BALIĞI (MASTACEMBALUSMASTACEMBALUS, BANK VE SOLANDER, 1794)'IN BÖBREKLERİN HİSTOLOJİK YAPISI - SUİÇER, EMRAH (Fırat Üniveristesi, 2023)
Bu araştırmada; 2014/113 protokol no'lu projede kullanılan 5 adet Mastacembelus mastacembelus' dan alınan böbrek dokularına ait parafin bloklar kullanılmıştır. Parafin bloklardan 5-6 mikron kalınlığında kesitler alındıktan sonra hematoksilen eosin, crosmann ve Periodic acid Shiff (PAS) boyamaları yapıldı. Boyamaları yapılan preparatlar ışık mikroskobunda incelendikten sonra mikrofotoğrafi ile görüntülendi. Mastacembelus mastacembelus'un böbreği vücut boşluğunun üst tarafında, omurgaların altında ince ve uzun iki lop şeklinde yumuşak bir çift organ olarak görüldü. Kırmızımsı kahverenginde ve ince bir zarla kaplı olduğu belirlendi. Her nefronda glomerulus ve glomerulusun etrafının Bowman kapsulu ile çevrildiği belirlendi. Ayrıca proksimal tubul, distal tubul ve toplayıcı tubullerin varlığı da gözlendi. Üriner tubullerin boyun segmenti, first ve second proksimal segmenti, distal segment ve toplayıcı kanallardan oluştuğu tespit edildi.

Histological examination of Mastacembelus mastacembelus (Bank and Solander, 1794) kidney caughted from Keban Dam Lake. In this study; Paraffin blocks of kidney tissues taken from 5 Mastacembelus mastacembelus used in the project with protocol number 2014/113 were used. After 5-6 micron thick sections were taken from paraffin blocks, hematoxylin, eosin, Crosmann and Periodic acid Shiff (PAS) stainings were performed. After the stained preparations were examined under a light microscope, they were visualized by microphotograph. The kidney of Mastacembelus mastacembelus was seen as a soft double organ in the form of two long and thin lobes under the vertebrae in the upper part of the body cavity. It was determined to be reddish brown and covered with a thin membrane. It was determined that the glomerulus and glomerulus were surrounded by Bowman's capsule in each nephron. In addition, the presence of proximal tubule, distal tubule and collecting tubules were also observed. It was determined that the urinary tubules consisted of neck segment, first and second proximal segment, distal segment and collecting ducts.
Histology structure of the kidneys of the spiny freshwater eel(Mastacembalus mastacembalus, bank and solander, 1974)
Keywords: Su Ürünleri